Physicians’ migration from Romania to France: a brain drain into Europe? - Raymonde Séchet (Unité Mixte de Recherche 8504 Géographie-cités, 2015)
The migration of highly skilled workers and more specifically of physicians has been a component of the globalisation of the recent few decades. In Europe, these physicians’ migration and mobility has increased with the dynamics of expansion of EU. Since 2007, many Romanian doctors have left their country to work in Western European Countries, especially in France where they either help to alleviate the lack of general practitioners in isolated rural areas, or work as specialists in hospitals. This paper analyses the results of a survey carried out on 182 Romanian physicians in three areas in France, national data, and a corpus of national and local newspaper articles. It appears that physicians’ motivations are both professional and familial, most of them, mainly women, having a long-term or a definitive migration project. The brain drain of Romanian doctors constitutes such a dramatic loss for the national healthcare provision that the hypothesis of a brain strain or of a brain gain cannot be retained. While clearly not generalizable to other parts of the world, the study of physicians’ migration from Romania to France has international significance as an illustration of globalisation in medical labour markets and of theories relating to migration of highly skilled workers, as well as spatial inequalities in healthcare.